Six Decades of The Accounting Review: A Summary of Author and Institutional Contributors. - Heck, J. Louis; Bremser, Wayne G. (The Accounting Review, 1986)
ABSTRACT: Publication of 'the October 1985 issue of The Accounting Review marked the culmination of the journal's first 60 years of contributions to the profession. This study identifies and summarizes the contributing authors, their academic affiliation, and where they earned their doctoral degrees. The authors, academic employers, and doctoral degree-granting institutions appearing most frequently in the journal are ordered for the entire 60-year period and for three 20-year subperiods.